Chemometric Comparison of Data Files Using Several Thermal Analytical Techniques for Dating Fossil Bones from Two Old Burial Sites - Tomassetti, Mauro; Martini, Elisabetta; Castrucci, Mauro; Campanella, Luigi; Coppa, Alfredo (Current Analytical Chemistry, 2021)
Background: The possibility of estimating the age of fossil bones using only classic thermogravimetry, on the basis of proper % mass loss ratio values, has been widely considered in the past years. Objective: Our research has brought some innovations to the previous background, by using chemometric methods and by processing the numerical files of whole thermogravimetric curves. The objective of this paper is the selection, among the main thermal analysis methods available, i.e., thermogravimetry (TG), derivative thermogravimetry (DTG), differential thermal analysis (DTA) and thermal dilatometry analysis (TDA), of the most suitable one, in order to evaluate the age of fossil bones. Methods: Fossil bone samples from two ancient cemeteries in Sudan were analyzed using different thermal methods (TG, DTG, DTA, and TDA). Data of whole recorded thermal curves have been processed by PCA analysis. Results: A systematic comparison of several thermal analytical techniques allowed to conclude that TG or DTG curves can provide more appropriate information to determine how old fossil bones of different ages are, as evidenced by PCA processing of the entire file set of TG or DTG curves. Conclusion: It can be concluded that the chemometric processing of TG or DTG curves data files is the best method; however, discussing other thermal analytical curves (DTA and TDA) can complete the information found by means of chemometric processing of whole TG and DTG curves.
Keywords: whole curves' data files